2019
DOI: 10.29245/2689-999x/2018/1.1146
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Ambient Temperature and Asthma Exacerbation in Children: A Systematic Review

Abstract: Background: Asthma is one of the most common chronic noncommunicable diseases which is seen more in the developed than developing countries of the world. Recurrence and exacerbations of the disease are common among patients and often lead to hospitalization and therapeutic interventions. Ambient air temperature might be related to the relapse of asthma. This review was conducted to investigate the relation between ambient temperature and exacerbations of asthma in children.Methods: Related articles were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Research dealing with the influence of meteorological factors on the incidence of exacerbation of asthma and other respiratory tract diseases is gaining greater interest 42,43 . Most researchers approach the issue through the prism of atmospheric contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Research dealing with the influence of meteorological factors on the incidence of exacerbation of asthma and other respiratory tract diseases is gaining greater interest 42,43 . Most researchers approach the issue through the prism of atmospheric contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that temperature and humidity may affect cardiovascular and respiratory disease exacerbations and traffic accidents. 2,32 In order to adjust the effect of temperature and humidity, as confounding variables, a natural cubic spline function with a degree of freedom 6 and 3 was used for temperature and humidity, respectively. 33 The degree of freedom was determined by minimizing the Akaike’s information criterion (AIC).…”
Section: Methodsmentioning
confidence: 99%
“…Asthma is one of the most common chronic non-communicable diseases [ 39 ]. The disease has differential diagnosis between the acute and the chronic.…”
Section: Discussionmentioning
confidence: 99%